Memória e persuasão na pintura de Adriana Varejão - Cerqueira, Fátima Nader Simões (2009)
Adriana Varejão‘s painting is directly related to the mingled way the artist moves between persuasion as strategy, which brings about baroque to nowadays not to be reintroduced, but as a reference of Brazil‘s artistic heritage, esthetics and culture. The